Antithyroid Antibodies Are Implicated in Epileptogenesis of Adult Patients With Epilepsy. Issue 26 (July 2015) - Tsai, Meng-Han; Fu, Ting-Ying; Chen, Nai-Ching; Shih, Fu-Yuan; Lu, Yan-Ting; Cheng, Mei-Yun; Chuang, Hung-Yi; Chuang, Yao-Chung; Mello., Carlos
<x xml:space="preserve">Abstract</x> Abstract Antithyroid antibodies (Abs) are associated with epilepsy in steroid-responsive encephalopathy, but have been rarely studied in unselected epilepsy patients. This study aimed to characterize the prevalence and associated factors of antithyroid Abs and other auto-Abs in adult patients with epilepsy. Epilepsy patients without autoimmune disorders were surveyed for antinuclear antibody (ANA), anti-β2 glycoprotein 1 antibody (aβ2GP1), anticardiolipin IgG Ab, antimicrosomal antibody (AMA), antithyroglobulin antibody (ATA), and thyroid function test. Of 319 patients, 75 (23.5%) were positive for at least 1 Ab. The most common Ab was anticardiolipin antibody (aCL) (30/319, 9.4%), followed by AMA (24/319, 7.5%), ANA (18/319, 5.6%), aβ2GP1 (18/319, 6.5%), and ATA (6/319, 3.25%). Antimicrosomal Abs were significantly more frequent in patients who were female, older at disease onset, older at the time of study, and had unknown seizure etiology. The presence of aCL was significantly associated with more frequent seizures. Most patients with antithyroid Ab were female and had focal seizures with unknown etiology. The association of different auto-Abs with different factors suggests that they may have different roles in adult patients with epilepsy. Recurrent seizures and certain antiepileptic medications may cause the production of aCL. The role of antithyroid Abs in adult focal epilepsy with unknown cause, especially in females, warrants further evaluation because of the potential implications on treatment.